The common pathways and targeted drugs for psoriasis and inflammatory bowel disease - Jinsheng LI; Yaqian ZHU; Yongfeng CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
The increasing evidence showed that psoriasis and inflammatory bowel disease are now considered as chronic systemic inflammatory diseases, and they are comorbidities for each other. Due to multiply overlapping pathophysiological mechanisms, drugs targeting to their common pathways have become hot spots in the current treatment of these two comorbidities. This review summarizes the common pathways involved in psoriasis and inflammatory bowel disease, including extracellular tumor necrosis factor, IL-23, IL-17 signaling pathways, as well as intracellular JAK-STAT pathway, cAMP signaling pathway, and ROR-γT/Th17 axis. Additional, this paper also briefly summarizes the drugs targeting to these common pathways. Altogether, the paper can provide some ideas for clinical treatment of these two comorbidities.